Manejo nutricional na cultura da soja : reflexos na produção e na qualidade da semente - Deuner, Cristiane (2013)
Soybean has great economic importance in agriculture as well as in Brazil and other cultures, productivity and profitability are key aspects. In this context, the use of seeds of good quality with high germination and vigor and in the appropriate dosage of fertilizers, plant available at the moment are demanded is very important to achieve an appropriate stand of plants, and seeds with satisfactory production quality. Thus, the present study aimed to evaluate the effect of fertilizer management through seed treatment and foliar application on yield components and physiological and sanitary quality of soybean seeds. The experimental design was a randomized block design with four replications and six treatments, constituting a witness and five different combinations of nutrients (CoMo, Whole, Potassium phosphite, Manganese and CaB), applied as seed treatment or via leaf at different times. The nutritional managements used did not favor the performance of soybean, including grain yield, physiological and sanitary quality of the seed produced. There is a higher incidence of fungi of the genera Penicillium spp. and Aspergillus spp.